The development and implementation of a new hospital performance measure to assess hospital contributions to community health and equity. (24th July 2022) - Plott, Caroline F.; Thornton, Rachel L. J.; Punwani, Ekta; Dankwa‐Mullan, Irene; Karunakaram, Hema; Craig, Kelly Jean Thomas; Rhee, Kyu; Sharfstein, Joshua M.
Abstract: Objective: To develop and implement a measure of how US hospitals contribute to community health with a focus on equity. Data Sources: Primary data from public comments and hospital surveys and secondary data from the IBM Watson Top 100 Hospitals program collected in the United States in 2020 and 2021. Study Design: A thematic analysis of public comments on the proposed measure was conducted using an iterative grounded approach for theme identification. A cross‐sectional survey of 207 hospitals was conducted to assess self‐attestation to 28 community health best practice standards in the revised measure. An analysis of hospital rankings before and after inclusion of the new measure was performed. Data Collection/Extraction Methods: Public comment on the proposed measure was collected via an online survey, email, and virtual meetings in 2020. The survey of hospitals was conducted online by IBM in 2021. The analysis of hospital ranking compared the 2020 and 2021 IBM Watson Top 100 Hospitals program results. Principal Findings: More than 650 discrete comments from 83 stakeholders were received and analyzed during measure development. Key themes identified in thematic analysis included equity, fairness, and community priorities. Hospitals that responded to a cross‐sectional survey reported meeting on average 76% of applicable best practice standards. Least met standards included providing emergent buprenorphine treatment for opioid use disorder (53%), supporting an evidence‐based home visiting program (53%), and establishing a returning citizens employment program (27%). Thirty‐seven hospitals shifted position in the 100 Top Hospital rankings after the inclusion of the new measure. Conclusions: There is broad interest in measuring hospital contributions to community health with a focus on equity. Many highly ranked hospitals report meeting best practice standards, but significant gaps remain. Improving measurement to incentivize greater hospital contributions to community health and equity is an important priority.